Application of the front tracking method in micro flow measuring devices. (October 2022) - Batista, Elsa; Sousa, João A.; Álvares, Miguel; Afonso, Joana; Martins, Rui F.
Abstract: This work has the main objective to develop a calibration method for micro flow measuring devices based on the front tracking principle, in the Volume and Flow Laboratory (LVC) of the Portuguese Institute of Quality (IPQ), in a partnership with and the Department of Mechanical and Industrial Engineering (DEMI) of The New University of Lisbon under the project MeDD II – Metrology for Drug Delivery. The experimental setup consists of using a camera and Python software to track the distance traveled by the meniscus of a liquid inside a capillary tube and calculate the flow rate according to appropriated equations. Experimental tests using a flow generator and a flow meter were carried out for different flow rates. Two different setups with cameras of different specifications were tested. To validate the developed front tracking method, internal comparisons using a Nexus pump and a Sensirion meter were performed with the gravimetric and interferometric methods already implemented at LVC. The results obtained by these two comparisons were consistent. This new developed method can therefore be used to calibrate flow devices from 1000 μL/h down to 1 μL/h with an uncertainty value from 2% to 7% ( k  = 2). The calibration procedure is easy to apply and can be used for both syringe and flow meters. This method is simple to implement in a laboratory and the setup is relatively cheap compared to the gravimetric or interferometric method. Finally, the front tracking method was applied to the calibration of an implantable insulin pump used by diabetic patients.